Pengaruh Kualitas Layanan yang diterima Daring (PESQ) dan Kepuasan Pelanggan (E- Saticfaction) Terhadap Kepercayaan Pelanggan (E-Trust) pada Niaga-El Lazada - Kartini, Iis; Yurindera, Novan; Triadi, Dali Cahyo (Portofolio: Jurnal Ekonomi, Bisnis, Manajemen, dan Akuntansi, 2024)
Abstract The investigation was carried out with the objective of understanding the impact of Customer Service and Satisfaction on Customer Trust in Niaga El-Lazada. The research methodology employed in this study is characterized by a quantitative descriptive approach. This particular study falls within the realm of descriptive and associative research due to the examination of variables and the presentation of a systematic overview of the facts and the correlation among the variables under scrutiny, specifically the impact of service and customer satisfaction on customer trust in El-Lazada commerce. A survey or questionnaire method was utilized as the research method. The study took place at the Unpi Cianjur Campus, focusing on students from the Faculty of Economics across different levels, with a total of 84 respondents participating as the sample. The sampling technique adopted a non-probability approach by selecting samples through the Slovin formula. Data analysis involved a 5% error rate, employing multiple regression analysis and fulfilling the prerequisites for the analysis test as well as the classical assumption test using the SPSS 26 software application. The findings of this research revealed that the Service variable has a statistically significant partial effect on the Customer Satisfaction variable at Niaga El-Lazada, as evidenced by a t-value of 6.084. The level of customer satisfaction has a partially positive or significant impact on the Customer Satisfaction variable at Niaga el-Lazada, with a tcount of 2.149. The combined impact of Customer Service and Satisfaction shows a positive and significant effect on the Customer Trust variable, with an Fcount of 49.856. The contribution of Customer Service and Satisfaction to the level of Customer Confidence is 92.4%. The remaining 7.6% is influenced by variables outside the scope of this study.Keywords: Service Influence, Customer Satisfaction and Customer Trust. Abstrak Penelitian ini bertujuan untuk menyelidiki dampak Layanan Pelanggan dan Kepuasan Pelanggan terhadap Kepercayaan Pelanggan dalam Perdagangan El-Lazada menggunakan pendekatan deskriptif kuantitatif. Penelitian ini melibatkan deskripsi dan asosiasi variabel untuk analisis, memberikan gambaran terstruktur fakta dan hubungan untuk mengeksplorasi efek Layanan dan Kepuasan Pelanggan terhadap Kepercayaan Pelanggan pada Perdagangan El-Lazada melalui survei yang dilakukan di UNPI Cianjur yang melibatkan mahasiswa Fakultas Ekonomi di berbagai tingkatan. Ukuran sampel terdiri dari 84 responden, dipilih menggunakan sampling non-probabilitas dengan Formula Slovin. Analisis data menggunakan tingkat kesalahan 5%, memanfaatkan analisis uji regresi berganda, analisis persyaratan uji kriteria, dan uji asumsi klasik melalui program SPSS 26. Temuan mengungkapkan bahwa variabel Pengaruh Layanan secara signifikan mempengaruhi variabel Kepuasan Pelanggan di El Lazada Commerce, dengan nilai 6.084. Selain itu, Kepuasan Pelanggan memiliki dampak positif dan signifikan terhadap Kepercayaan Pelanggan di Commerce El-Lazada, dengan nilai 2,149. Efek gabungan dari Layanan dan Kepuasan Pelanggan juga secara signifikan mempengaruhi Kepercayaan Pelanggan, dengan nilai 49.856. Layanan dan Kepuasan Pelanggan secara kolektif berkontribusi 92,4% terhadap tingkat Kepercayaan Pelanggan, sementara sisanya 7,6% dikaitkan dengan variabel lain di luar ruang lingkup penelitian ini.Kata Kunci: Pengaruh Layanan, Kepuasan Pelanggan dan Kepercayaan Pelanggan.